SIAF: um sistema de informação, a ser integrado num ambiente de computação ubíqua, para gerenciamento de atividade física - Portocarrero, Jesús Martín Talavera (2010)
The World Health Organization (WHO) recommends performing regular physical activities as a way to combat the population inactivity. In São Carlos-SP municipality such activities are promoted by the health units and generate a large amount of data that needs processing. The aim of this work are to develop and evaluate an information system for managing physical activity data of the population enrolled to the São Carlos-SP health units, allowing for the generation of health and performance indicators, which will support the planning of public policies for the promotion of physical activity. Qualitative researches and field observations were conducted in order to capture the system requirements, and quantitative researches were done for its evaluation. This system was developed in Java using the Netbeans IDE 6.7.1. tool, and has interfaces that allow the management of the health units, physical activity groups, physical activity sessions, participants, and the caregivers responsible for these groups. For evaluating the system interfaces and usability, SAM questionnaires were applied to caregivers, with the following results: 84.44% for Satisfaction, 78.89% for Motivation, and 92.22% for Control Sense. For evaluating other system characteristics, a QUIS based questionnaire was applied to these same caregivers, with the following results in a 1-5 scale: 4.0 for Ease of Use, and 4.6 for Utility. This system has proved to be useful and easy to use, and its main contribution is to support the WHO recommendation for the practice of regular physical activity, since it provides the computational means for the effectiveness evaluation of physical activity groups of the São Carlos-SP health units.